2000
DOI: 10.3998/ark.5550190.0001.108
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted, facile route to 1H-pyrazolo[3,4-b]quinolines

Abstract: Aromatic aldehydes have been reported to react with 5-anilinopyrazoles in the presence of ZnCl 2 to give the corresponding benzylidenopyrazoles. In this paper evidence is given that the corresponding products are, in fact, 1H-pyrazolo [3,4-b]quinolines. This observation opens a novel route to these compounds. They show a blue emission in the solid state and, therefore, they are useful blue luminophores for electroluminescent devices. The synthetic procedure reported in the literature was significantly modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The author reported in the publication that he obtained two derivatives of this kind. However, later research by Tomasik et al showed that the actual products formed in this reaction were 1H-pyrazolo [3,4-b]quinolines 7 [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The author reported in the publication that he obtained two derivatives of this kind. However, later research by Tomasik et al showed that the actual products formed in this reaction were 1H-pyrazolo [3,4-b]quinolines 7 [32].…”
Section: Resultsmentioning
confidence: 99%
“…However, later research by Tomasik et al showed that the actual products formed in this reaction were 1H-pyrazolo[3,4-b]quinolines 7[32].…”
mentioning
confidence: 99%
“…The syntheses described by Michaelis were repeated, and the chemical structures of the compounds that were obtained were analysed by using 1 H NMR spectroscopy. It turned out that the structure of Michaelis 134 did not correspond to any of the compounds that he received, but that it did match the pyrazoloquinolines of 65 [87].…”
Section: H-pyrazolo[34-b]quinoline Syntheses Based On 5-arylaminoamin...mentioning
confidence: 99%
“…The syntheses described by Michaelis were repeated, and the chemical structures of the compounds that were obtained were analysed by using 1 H NMR spectroscopy. It turned out that the structure of Michaelis 134 did not correspond to any of the compounds that he received, but that it did match the pyrazoloquinolines of 65 [87]. In 1911, Michaelis heated 5-N-arylamino-1,3-disubstituted pyrazoles 132 with some aromatic aldehydes 133 in the presence of anhydrous ZnCl 2 and obtained compounds to which he assigned a structure 134 (Scheme 37) [1].…”
Section: H-pyrazolo[34-b]quinoline Syntheses Based On 5-arylaminoamin...mentioning
confidence: 99%
“…Reaction of acid hydrazide and its derivatives reacted with ethylaceto acetate or acetyl acetone or diethyl malonate produced pyrazole derivatives (13) .…”
Section: Introductionmentioning
confidence: 99%